DAMPAK PENGGUNAAN ARTIFICIAL INTELLIGENCE TERHADAP ETIKA AKADEMIK DAN KEJUJURAN SISWA - M. Naufal (PT. Habe Cendekia Utama, 2025)
The rapid development of Artificial Intelligence (AI) in the Education 4.0 era has encouraged educational institutions to integrate this technology into the learning process, but it has also raised new issues related to academic ethics and student honesty. Research shows that students are increasingly using AI to prepare assignments, answer questions, and produce academic work, potentially strengthening or weakening academic integrity depending on how it is used. This study aims to analyze the impact of AI use on student academic ethics and honesty, and to examine the role of schools and teachers in guiding the ethical use of AI. The method used was descriptive qualitative research, with data collection techniques through indepth interviews, observations, and documentation studies of students, teachers, and school policies related to AI use. The results show that AI has a positive impact in terms of improving conceptual understanding, efficiency, and independence in learning, and supporting integrity through plagiarism detection systems. However, on the other hand, AI is also being used as a means of academic cheating, such as AI-based plagiarism and submitting assignments without student intellectual involvement. This study confirms that clear school policies, the integration of character education and digital ethics, and consistent teacher guidance are key factors in ensuring AI functions as a learning partner that strengthens students' academic ethics and honesty.